Biodegradation of o-dichlorobenzene by Bacillus cereus DL-1：kinetics, degradation pathway, biodegradability and performance in biotrickling filter. Issue 1 (1st January 2020) - Yang, Bairen; Li, Yue; Shang, Qingqing; Ding, Cheng; Xu, Qi
ABSTRACT: o: -Dichlorobenzene could be mineralized as the sole carbon and energy source by Bacillus cereus DL-1. In this work, Haldane–Andrews and pseudo-first-order models were used to simulate the growth and degradation abilities of the strain. Two possible degradation pathways were identified by GC/MS intermediate and open-loop analysis. The removal efficiency (RE) of biotrickling filter (BTF) could reach 57.86% at the start phase. At the steady phase, the effects of empty bed residence time (EBRT), inlet gas concentration and intake load rate (ILR) on the performance of BTF have highlighted the potential of strain DL-1 for the treatment of o -dichlorobenzene.